Mucuna pruriens cannot develop phytoremediation of tebuthiuron in agricultural soil with vinasse: a morphometrical and ecotoxicological analysis - Frias, Yanca Araujo [UNESP]; Lima, Edivaldo Wilson [UNESP]; Aragão, Munick Beato [UNESP]; Nantes, Laura Silva [UNESP]; Moreira, Bruno Rafael Almeida [UNESP]; Cruz, Victor Hugo [UNESP]; Tomaz, Rafael Simões [UNESP]; Lopes, Paulo Renato Matos [UNESP] (Frontiers, 2023)
Pesticides offer stakeholders cost-effective solutions to control weeds. Nevertheless, such active compounds can manifest as severe environmental pollutants when escaping from agroecosystems into surrounding natural ecosystems, driving the need to remediate them. We, hence, analyzed whether Mucuna pruriens can develop a potential phytoremediator for treating tebuthiuron (TBT) in soil with vinasse. We exposed M. pruriens to microenvironments containing tebuthiuron at 0.5, 1, 1.5, and 2 (standard dose) L ha−1 and vinasse at 75, 150 (industrial recommendation), and 300 m3·ha−1. Experimental units without organic compounds represented controls. We assessed M. pruriens for morphometrical features, such as plant height and stem diameter and shoot/root dry mass, over approximately 60 days. We obtained evidence for M. pruriens not effectively removing tebuthiuron from the terrestrial medium. Such a pesticide developed phytotoxicity, significantly limiting its germination and growth. The higher the dose, the more negatively the tebuthiuron impacted the plant. In addition, introducing vinasse into the system, irrespective of volume, intensified the damage to photosynthetic and non-photosynthetic structures. Equally important, its antagonist action further decreased the production and accumulation of biomass. As M. pruriens could not effectively extract tebuthiuron from the soil, it could allow neither Crotalaria juncea nor Lactuca sativa to grow on synthetic media containing residual pesticide. An atypical performance of such testing (tebuthiuron-sensitive) organisms over independent ecotoxicological bioassays validated inefficient phytoremediation. Hence, M. pruriens could not offer a functional remediative option to treat environmental pollution by tebuthiuron in agroecosystems where vinasse occurs, such as sugarcane-producing areas. Although M. pruriens considered a tebuthiuron phytoremediator as cited in the literature, satisfactory results did not occur in our research due to high concentrations of vinasse in the soil. Therefore, this information requires more specific studies about the influence of high concentrations of organic matter on M. pruriens productivity and phytoremediation performance.
Keywords: bioremediation; ecotoxicology; green manure; herbicide; organic compound